The flora of the Assyrian monuments and its outcomes - Bonavia, Emanuel (A. Constable, 1894)
Flora of the Assyrian monuments of the British Museum, and others. - The Sacred trees of Assyria. - The cone fruit. - The lotus. - The evil eye. -The Trident. - Notes on some cylinders.